Ex Utero Intrapartum Treatment of Fetal Micrognathia. Issue 6 (1st June 2014) - DaValle, Brandon; Nagel, Erik; Gonzalez, Sara; Gaconnet, Cory; Latendresse, Thomas; You, Whitney; Johnson, Christopher; Brigger, Matthew
ABSTRACT: Background: Ex utero intrapartum treatment (EXIT) procedures have emerged as a viable option for potentially life-saving procedures in fetuses with predicted airway compromise at birth. The ability to maintain maternal-fetal uteroplacental perfusion allows for prolonged procedures in a stable fetal hemodynamic environment thereby avoiding neonatal hypoxemia or sequelae of an emergent tracheostomy. Case: A 26-year-old female presents with a 20-week ultrasound and subsequent magnetic resonance imaging demonstrating severe fetal micrognathia (jaw index below the 5th percentile), glossoptosis, polyhydramnios, absence of a gastric bubble, and suspected microtia concerning for Treacher Collins syndrome. An EXIT procedure was completed with successful intrapartum endotracheal intubation with a flexible fiber-optic bronchoscope through a laryngeal mask airway. Conclusion: This case represents the first EXIT procedure completed at Naval Medical Center San Diego. Although this case is unique, the clinical skills and coordination of care required to perform this procedure are exemplified in our daily practice of stabilizing, transporting, and definitively treating our wounded warriors. The ability to work in coordination across multiple armed services to provide the EXIT procedure to our military families, for potentially life-saving procedures, is a true testament to the current state of Military Medicine.